2023
DOI: 10.3724/abbs.2023005
|View full text |Cite
|
Sign up to set email alerts
|

lncRNA LINC00960 promotes apoptosis by sponging ubiquitin ligase Nrdp1-targeting miR-183-5p

Abstract: The ubiquitin ligase Nrdp1/RNF41 promotes the ubiquitin-dependent degradation of multiple important substrates, including BRUCE/BIRC6, a giant ubiquitin-conjugating enzyme inhibiting both apoptosis and autophagy. miR-183-5p is associated with various malignancies potentially by targeting dozens of genes. Here, we show that the lncRNA LINC00960 binds to the Nrdp1-targeting miR-183-5p and promotes apoptosis. Compared to other known miR-183-5p targets, Nrdp1 mRNA is among the few with top scores to complement miR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 60 publications
0
1
0
Order By: Relevance
“…During exosome biogenesis, RNA molecules including miRNA are selectively packaged into sEV [54] , and many studies have reported that the EV RNA profiles differ profoundly from those of their cells of origin [55] . The vesicular membrane protects many unstable small RNA species [56,57] and usually inhibits their activity on target RNA sequences via 3'UTR direct binding [58,59] . Transforming growth factor-beta-3 (TGFβ3) mRNA's 3'UTR site is a direct target of miR-381-3p [46] .…”
Section: The Sev Isolation Methodology Influences the Expression Leve...mentioning
confidence: 99%
“…During exosome biogenesis, RNA molecules including miRNA are selectively packaged into sEV [54] , and many studies have reported that the EV RNA profiles differ profoundly from those of their cells of origin [55] . The vesicular membrane protects many unstable small RNA species [56,57] and usually inhibits their activity on target RNA sequences via 3'UTR direct binding [58,59] . Transforming growth factor-beta-3 (TGFβ3) mRNA's 3'UTR site is a direct target of miR-381-3p [46] .…”
Section: The Sev Isolation Methodology Influences the Expression Leve...mentioning
confidence: 99%